Hepatocyte Growth Factor Releases Mink Epithelial Cells from Transforming Growth Factor β1-Induced Growth Arrest by Restoring Cdk6 Expression and Cyclin E-Associated Cdk2 Activity - Tsubari, Minna (American Society for Microbiology, 1999)
Transforming growth factor β (TGF-β) potently suppresses Mv1Lu mink epithelial cell growth, whereas hepatocyte growth factor (HGF) counteracts TGF-β-mediated growth inhibition and induces Mv1Lu cell proliferation (J. Taipale and J. Keski-Oja, J. Biol. Chem. 271:4342–4348, 1996). By addressing the cell cycle regulatory mechanisms involved in HGF-mediated release of Mv1Lu cells from TGF-β inhibition, we show that increased DNA replication is accompanied by phosphorylation of the retinoblastoma protein and alternative regulation of cyclin-Cdk-inhibitor complexes. While TGF-β treatment decreased the expression of Cdk6, this effect was counteracted by HGF, followed by partial restoration of cyclin D2-associated kinase activity. Notably, HGF failed to prevent TGF-β induction of p15 and its association with Cdk6. However, HGF reversed the TGF-β-mediated decrease in Cdk6-associated p27 and cyclin D2-associated Cdk6, suggesting that HGF modifies the TGF-β response at the level of G(1) cyclin complex formation. Counteraction of TGF-β regulation of Cdk6 by HGF may in turn affect the association of p27 with Cdk2-cyclin E complexes. Though HGF did not differentially regulate the total levels of p27 in TGF-β-treated cells, p27 immunodepletion experiments suggested that upon treatment with both growth factors, less p27 is associated with Cdk2-cyclin E complexes, in parallel with restoration of the active form of Cdk2 and the associated kinase activity. The results demonstrate that HGF intercepts TGF-β cell cycle regulation at multiple points, affecting both G(1) and G(1)-S cyclin kinase activities.